2020
DOI: 10.1111/ppl.13227
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotection and optimization of sucrose usage contribute to faster recovery of photosynthesis after water deficit at high temperatures in wheat

Abstract: Plants are increasingly exposed to events of elevated temperature and water deficit, which threaten crop productivity. Understanding the ability to rapidly recover from abiotic stress, restoring carbon assimilation and biomass production, is important to unravel crop climate resilience. This study compared the photosynthetic performance of two Triticum aestivum L. cultivars, Sokoll and Paragon, adapted to the climate of Mexico and UK, respectively, exposed to 1-week water deficit and high temperatures, in isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 86 publications
0
10
1
Order By: Relevance
“…Previous studies have shown that the photosynthesis of plants recovers fast after the release of thermal stress of 38°C (Correia et al 2021). Our research shows that after removing 10 d of thermal stress, the photosynthesis of plants did not recover but showed a further reduction, especially in heat-sensitive variety.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Previous studies have shown that the photosynthesis of plants recovers fast after the release of thermal stress of 38°C (Correia et al 2021). Our research shows that after removing 10 d of thermal stress, the photosynthesis of plants did not recover but showed a further reduction, especially in heat-sensitive variety.…”
Section: Discussioncontrasting
confidence: 63%
“…Chl fluorescence is used to assess the effects of environmental changes on photosynthesis indirectly. It has been reported that PSII has high thermal sensitivity (Dash and Mohanty 2001, Sharkey 2005, Correia et al 2021, but high temperatures below 40℃ do not seriously affect PSII activity (Allakhverdiev et al 2008). The ratio of variable fluorescence to maximum fluorescence (F v/Fm) determines the maximum quantum efficiency of PSII, while low Fv/Fm under stress indicates damage to the PSII reaction center.…”
Section: Discussionmentioning
confidence: 99%
“…The cropping of soybean occurs during the spring/summer seasons, which in tropical regions corresponds to the months of September–March. While this period is usually hot and rainy in tropical regions, short dry spells occur frequently during soybean cropping [ 51 ], causing a short period of stress due to lack of water and or high temperatures [ 52 ], especially in the phenological stages after flowering, as observed in our study ( Figure 1 ). In the case of maize, its cropping occurs during the autumn/winter seasons (April-August), a period characterized by mild temperatures and a dry climate.…”
Section: Discussionmentioning
confidence: 57%
“…However, P0023 and P9838 showed opposing trends in the response of ETo/RC to water stress (Figure 2c), with the electron transport rate per reaction center decreasing in the former and increasing in the latter (p < 0.05), suggesting that the resilience to oxidative stress (absence of RC inactivation) comes together with a lower photochemical activity. Furthermore, in wheat, Correia et al [58] found a strong correlation between these energy fluxes and the antioxidant capacity of leaves under drought stress. Since drought stress causes the loss of photosynthetic reaction centers, the loss of chlorophyll a content detected in all except P0023 plants during S2 was expected.…”
Section: Discussionmentioning
confidence: 97%